Properties of Concrete Using Bottom Ash N107 Cured in The Tidal Zone - Enda, Dedi; Febriani, Oni; Lisya, Mutia (Journal of Structural Monitoring and Built Environment, 2022)
In Indonesia, around 9.89 million tons of FABA waste is generated annually from burning coal in steam power plants (PLTU). One type of FABA waste categorized as Non-B3 which is Bottom Ash with a waste code of N107. If this waste not utilized, it will only become a waste product. With the Indonesia Government Regulation No. 22 of 2021, this waste utilization process becomes more manageable and has the opportunity to be optimized. One of the recommended alternative uses of Non-B3 FABA is substituting raw materials for infrastructure materials, especially for coastal areas where it is difficult to obtain fine aggregate or sand. In the process of development, coastal areas are often in contact with sea air. Seawater has a high salt content which can undermine the strength and durability of concrete, so this study focuses on discussing the effect of using Bottom Ash as a sand substitute on concrete strength of the M20 concrete, which is influenced by the sea’s tides. By using the ACI 211.1-91 concrete mix design method, experimental concrete samples were made by substituting sand with bottom ash N107 with a percentage of 0% to 100% in the range of 10% and a maximum coarse aggregate size of 20 mm, the treatment of concrete samples was carried out in freshwater and in the tidal zone. The results showed that the optimum compressive strength at using bottom ash of 20% - 30% as a substitute for sand with a heavy volume of concrete decreased with the increase in the bottom ash percentage. From the sample of concrete with the optimum compressive strength, it is known that the porosity of the concrete immersed in the tidal zone is higher than that of the concrete immersed in fresh water. For concrete that was given maintenance treatment in the tidal zone, the compressive strength decreased at 56 days.